Bartonella Seroepidemiology in Dogs from North America, 2008–2014. (2nd December 2017) - Lashnits, E.; Correa, M.; Hegarty, B.C.; Birkenheuer, A.; Breitschwerdt, E.B.
Abstract : Background: Improved understanding of Bartonella species seroepidemiology in dogs may aid clinical decision making and enhance current understanding of naturally occurring arthropod vector transmission of this pathogen. Objectives: To identify demographic groups in which Bartonella exposure may be more likely, describe spatiotemporal variations in Bartonella seroreactivity, and examine co‐exposures to other canine vector‐borne diseases (CVBD). Animals: A total of 15, 451 serology specimens from dogs in North America were submitted to the North Carolina State University, College of Veterinary Medicine Vector Borne Disease Diagnostic Laboratory between January 1, 2008, and December 31, 2014. Methods: Bartonella henselae, Bartonella koehlerae, and Bartonella vinsonii subspecies berkhoffii indirect fluorescent antibody (IFA) serology results, as well as results from a commercial assay kit screening for Dirofilaria immitis antigen and Ehrlichia species, Anaplasma phagocytophilum, and Borrelia burgdorferi antibodies, and Ehrlichia canis, Babesia canis, Babesia gibsoni, and Rickettsia species IFA results were reviewed retrospectively. Results: Overall, 3.26% of dogs were Bartonella spp. seroreactive; B. henselae (2.13%) and B. koehlerae (2.39%) were detected more frequently than B. vinsonii subsp. berkhoffii (1.42%, P  < 0.0001). Intact males had higher seroreactivity (5.04%) than neutered males (2.87%, P  < 0.0001) or intact or spayed females (3.22%, P  = 0.0003). Mixed breed dogs had higher seroreactivity (4.45%) than purebred dogs (3.02%, P  = 0.0002). There was no trend in seasonal seroreactivity; geographic patterns supported broad distribution of exposure, and co‐exposure with other CVBD was common. Conclusions and Clinical Importance: Bartonella spp. exposure was documented throughout North America and at any time of year. Male intact dogs, mixed breed dogs, and dogs exposed to other CVBD have higher seroreactivity to multiple Bartonella species.